PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA FINANCIAL (Study Pada Perusahaan Jasa di Kota Pekanbaru Provinsi Riau) - Azlina, Nur; Sulaeman, Dinanda (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study aimed to determine the effect of total quality management practices on the performanceof the company´s financial services in Pekanbaru city of Riau Province. The study was conductedin 67 service companies that have implemented total quality management practices for over threeyears. The company consists of 33 banking companies, 12 manufacturing companies, 16 hospitalsand 6 telecom companies. Sampling was carried out using non-probability sampling methods(purposive sample method) while the data collection techniques performed by direct methods. Thetest data used for multiple linear regression. Results showed that of the six dimensions of TQMdianailsa only variable customer focus and management of human resources that do not affect theperformance of the financial while others are leadership, process management, strategic planningas well as information and analysis of the influence financial performance.Keywords: leadership, focus on customers, human resource management, process management,strategic planning, information analysis, and performance financial